2020
DOI: 10.2147/cmar.s238530
|View full text |Cite
|
Sign up to set email alerts
|

<p>A New Nomogram Based on Early Postoperative NLR for Predicting Infectious Complications After Gastrectomy</p>

Abstract: Purpose: Our study aimed to construct a visible model to evaluate the risk of infectious complications after gastrectomy. Methods: The clinical data of 856 patients who underwent gastrectomy were used to retrieve medical records. Univariate and multivariate analyses were performed to correlate early postoperative NLR and operative variables with postoperative complications, and the construction of the nomogram was based on logistic regression. The concordance index and receiver operating characteristic curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
(60 reference statements)
0
2
0
3
Order By: Relevance
“…We found nutritional improvement in the FJT group and did not observe major effects on postoperative adverse outcomes. The NLR was measured as an indicator of systemic inflammation (29); the gradual increase in lymphocytes and the gradual decline in neutrophils occurs with systemic inflammatory reaction improvement (30). The OPNI is a simple and effective nutritional assessment and surgical risk prediction index that is currently widely used in gastrointestinal surgery (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…We found nutritional improvement in the FJT group and did not observe major effects on postoperative adverse outcomes. The NLR was measured as an indicator of systemic inflammation (29); the gradual increase in lymphocytes and the gradual decline in neutrophils occurs with systemic inflammatory reaction improvement (30). The OPNI is a simple and effective nutritional assessment and surgical risk prediction index that is currently widely used in gastrointestinal surgery (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, preoperative NLR and PLR have been investigated as independent prognostic factors that determine cancer progression and recurrence [ 23 , 24 ]. Additionally, postoperative NLR was reported as an independent risk factor of postoperative complications and survival in some cancers [ 18 , 19 , 20 , 25 ]. Surprisingly, few studies have reported an association between postoperative NLR changes and surgical outcomes for cervical cancer according to the surgical method.…”
Section: Discussionmentioning
confidence: 99%
“…Relación de la supervivencia de los pacientes con los niveles de los biomarcadores La gastrectomía hoy en día continúa siendo el tratamiento principal para los tumores gástricos y se tiene que la morbilidad de los pacientes después de someterse al procedimiento va entre el 17,4% y el 37% (6). El cambio posoperatorio de la NLR es un reflejo del comportamiento entre la respuesta inflamatoria de la persona y la respuesta inmunitaria posterior al tratamiento.…”
Section: Relación Entre Los Biomarcadores Y El Cáncer Gástricounclassified
“…La gastrectomía es uno de los tratamientos más utilizados en la actualidad para el tratamiento de las neoplasias malignas gástricas, entre ellas destacan la gastrectomía total (GT), subtotal (GST) y parcial (6).…”
Section: Introductionunclassified
See 1 more Smart Citation